Paste Fills Technology in Condition of Estonian Oil Shale Mine (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Oil shale mining and processing industry in Estonia produce a wide assortment of waste could be considered as available fill materials. Waste rock which is not usable in civil engineering and road building may be used for backfilling underground mines. Paste fills technology, which has several benefits, requires careful selection of oil shale waste rock aggregates and other carbonate stones. The laboratory tests and theoretical investigations were made for determination the applicability of limestone and dolostone aggregates as backfill material. It enables to determine the feasible parameters of aggregates from oil shale mining waste rock. Analysis showed that limestone aggregates of Estonian oil shale mines suit best for backfill technology in conditions.